Deubiquitination of epidermal growth factor receptor by ubiquitin-specific peptidase 54 enhances drug sensitivity to gefitinib in gefitinib-resistant non-small cell lung cancer cells - Mi Seong Kim; Min Seuk Kim (PLoS ONE, 2025)
A precise balance between ubiquitination and deubiquitination is crucial for cellular regulation. Ubiquitin-specific peptidase 54 (USP54), an active deubiquitinase (DUB), modulates the ubiquitination of the epidermal growth factor receptor (EGFR). While the significance of USP54 in tumorigenesis is known, its specific function in cancer progression remains unclear. This study investigates the role of USP54 in gefitinib sensitivity in gefitinib-resistant non-small cell lung cancer (NSCLC) cells. Using western blotting and next-generation sequencing, we examined gene expression changes in ubiquitination pathways. USP54 deficiency and its impact on cell viability and gefitinib response were evaluated in 2D and 3D spheroid cancer models. Prolonged gefitinib exposure altered the expression of 20 deubiquitinase-regulating genes. Notably, ubiquitin C-terminal hydrolase L3, downregulated by gefitinib, was identified as a key regulator of EGFR ubiquitination in gefitinib-sensitive PC9 cells. Silencing USP54 in resistant NSCLC cells increased gefitinib-induced EGFR ubiquitination and G0/G1 cell cycle arrest, enhancing drug susceptibility in resistant spheroids. USP54 upregulation in gefitinib-treated cells was associated with reduced EGFR ubiquitination, stabilizing EGFR and promoting cell survival. These findings suggest USP54 as a critical modulator of EGFR stability and a potential therapeutic target to overcome gefitinib resistance in NSCLC.